2020
DOI: 10.1089/heq.2020.0025
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Bias in Counseling for Permanent Contraception: Historical Context and Recommendations for Counseling

Abstract: We provide an overview of the causes, manifestations, and potential mitigating steps regarding implicit bias in counseling for permanent contraception. The historical context of sterilization abuses and the implications of these on society's notions of fitness for parenthood are reviewed. We present contemporary examples of contraceptive coercion and discuss the impact of implicit bias from health care providers. Finally, we outline steps for ensuring a patient-centered shared decision-making ethical approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Educational strategies regarding HIV-prevention tools with clinicians and also with all sexually active women are warranted. 91 Although HIV screening for sexually active women during gynecology visits is supported without copays, fewer than 20% of sexually active women reported receiving an HIV test during the past year in a recent report. 96 Offering routine HIV screenings should be fully incorporated during obstetrics and gynecology visits; early diagnosis is vital for timely treatment and decreased morbidity and mortality (Fig.…”
Section: Reproductive Health Disparities Access Services and Outcomentioning
confidence: 99%
“…Educational strategies regarding HIV-prevention tools with clinicians and also with all sexually active women are warranted. 91 Although HIV screening for sexually active women during gynecology visits is supported without copays, fewer than 20% of sexually active women reported receiving an HIV test during the past year in a recent report. 96 Offering routine HIV screenings should be fully incorporated during obstetrics and gynecology visits; early diagnosis is vital for timely treatment and decreased morbidity and mortality (Fig.…”
Section: Reproductive Health Disparities Access Services and Outcomentioning
confidence: 99%
“…Although studies have found mixed results regarding whether including training during residency helps with overall IUD insertion [37,38], continuing education for physicians was found to be a strong predictor of LARC insertion [39]. Efforts to improve contraceptive rates need to a) consider ways to address cost, especially for postpartum LARC; b) create strategies to reduce physician bias [40] and misconceptions regarding promoting LARC; and c) provide culturally tailored patient education.…”
Section: Multinomial Logistic Regression Estimating the Odds Of Contraception Usementioning
confidence: 99%
“…Data suggest that women of color are offered LARC more often sometimes owing to implicit biases. 91 Awareness of historical and modern-day racial injustices often contribute to the lower rate of contraceptive use among Black and Hispanic women; there is a distrust by some patients that has yet to be acknowledged by many clinicians. 92 To combat this, patient-centered shared decision making is a vital component of all contraceptive counseling.…”
Section: 72mentioning
confidence: 99%
“…Educational strategies regarding HIV-prevention tools with clinicians and also with all sexually active women are warranted. 91 Although HIV screening for sexually active women during gynecology visits is supported without copays, fewer than 20% of sexually active women reported receiving an HIV test during the past year in a recent report. 96 Offering routine HIV screenings should be fully incorporated during obstetrics and gynecology visits; early diagnosis is vital for timely treatment and decreased morbidity and mortality (Fig.…”
Section: Human Immunodeficiency Virus Diagnosesmentioning
confidence: 99%